1995
DOI: 10.1016/s0886-3350(13)80134-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term decentration of intraocular lenses implanted with envelope capsulotomy and continuous curvilinear capsulotomy: A comparative study

Abstract: Intraocular lens (IOL) decentration was studied in a series of 569 consecutive eyes that had extracapsular cataract extraction (ECCE) and posterior chamber IOL implantation. In 383 of the eyes, an envelope capsulotomy (EC) was performed; in 186, a continuous curvilinear capsulotomy (CCC). In 33 eyes, the anterior capsule had one radial tear that reached the lens equator. In all eyes, IOL decentration was determined more than six months after surgery. Mean IOL decentration was 0.42 +/- 0.02 mm in the EC eyes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Conventional CCC was shown to be safer and less likely to be associated with anterior capsular tears than a can opener or linear capsulotomy, 18 and showed less IOL decentration and tilt. [19][20][21] Even with an intact CCC, asymmetric capsular shrinkage, which is affected by capsulotomy shape, increases IOL decentration. 22 Furthermore, the size of the capsulotomy and the area and regularity of anterior capsule-IOL overlap infl uence the IOL position.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional CCC was shown to be safer and less likely to be associated with anterior capsular tears than a can opener or linear capsulotomy, 18 and showed less IOL decentration and tilt. [19][20][21] Even with an intact CCC, asymmetric capsular shrinkage, which is affected by capsulotomy shape, increases IOL decentration. 22 Furthermore, the size of the capsulotomy and the area and regularity of anterior capsule-IOL overlap infl uence the IOL position.…”
Section: Resultsmentioning
confidence: 99%
“…Centration of the IOL is considered to be related to many lens characteristics including design, total length, and optic and haptic materials (18). Several studies reported that an asymmetric capsulorhexis or any radial tear of anterior capsule possibly cause IOL decentration (19)(20)(21). Asymmetric bag-sulcus lens fixation (22) or broken haptics also lead to severe IOL dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetric shrinkage can be prevented with newer techniques such as continuous curvilinear capsulotomy [4] or high-frequency diathermy of the anterior capsule. When recognised early, extended shrinkage of the anterior capsulorhexis can managed relatively easily by making incomplete radial incisions in the anterior capsule with the Nd:YAG laser.…”
Section: Discussionmentioning
confidence: 99%